2008
DOI: 10.1103/physrevlett.101.235001
|View full text |Cite
|
Sign up to set email alerts
|

Convective Dust Clouds Driven by Thermal Creep in a Complex Plasma

Abstract: Steady-state clouds of microparticles were observed, levitating in a low-frequency glow discharge generated in an elongated vertical glass tube. A heated ring was attached to the tube wall outside, so that the particles, exhibiting a global convective motion, were confined vertically in the region above the location of the heater. It is shown that the particle vortices were induced by the convection of neutral gas, and the mechanism responsible for the gas convection was the thermal creep along the inhomogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…2(b) is often seen in experiments on spatially extended dust clouds and may possibly derive from intrinsic plasma forces 13 or unwanted thermal gradients due to the tempered electrodes. 25 Performing both the extinction measurement and the laser slice technique simultaneously, dynamical phenomena such as dust density waves can be investigated with respect to their global and local properties. 27…”
Section: Extinction Measurementmentioning
confidence: 99%
“…2(b) is often seen in experiments on spatially extended dust clouds and may possibly derive from intrinsic plasma forces 13 or unwanted thermal gradients due to the tempered electrodes. 25 Performing both the extinction measurement and the laser slice technique simultaneously, dynamical phenomena such as dust density waves can be investigated with respect to their global and local properties. 27…”
Section: Extinction Measurementmentioning
confidence: 99%
“…Therefore it is proportional to the thermal conductivity of the gas κ T , the temperature gradient and the squared particle radius: F th ∝ a 2 κ T ∇T N . Thermophoresis can be used to levitate particles in a plasma chamber against gravity into regions in the bulk plasma, providing similar conditions as experiments in microgravity, and it can lead to other interesting phenomena such as convection, circulations and formation of structures [107,108,109,110].…”
Section: Forcesmentioning
confidence: 99%
“…Vaulina et al 4,[16][17][18] and Samarian et al 19 attributed that dust charge gradient in an inhomogeneous plasma in the presence of a non-electrostatic force orthogonal to it causes an instability which leads to the formation of the dust vortices. Mittic et al 20 reported the formation of dust vortices due to thermal creep flow (TCF) in a low frequency discharge produced in an inhomogeneously heated vertical glass tube at low pressures. Later, Flanagan et al 21 designed an experiment to isolate TCF from other temperature gradient driven effects and verified its role on vorticity formation at low pressures.…”
Section: Introductionmentioning
confidence: 99%